Tingkat Instabilitas Komoditi Ekspor Nonmigas di Indonesia Periode 2007Q1-2015Q4 - Lilis Yuliati; Shofiyya Farras Setyawan; Fajar Wahyu Prianto (UPT Penerbitan Universitas Jember, 2017)
The purpose of this study was to assess the value of non-oil export instability in Indonesia and to determine the dominant factor affecting the movement of the level of instability in Indonesia's non-oil exports. The data used in this research is secondary data obtained from the central bank and the relevant agencies. The analytical tool used in this research is the index of instability of exports to the data time series. The objects of this study are value, volume and price of non-oil exports in Indonesia 2007Q1-2015Q4 period. The results of this study is the movement of the value of non-oil exports in Indonesia are relatively stable or have a low level of instability and the dominant affecting factor is the volume of exports. Keywords: Instability of exports, instability indexes, non-oil, export